Low but not undetectable early postoperative nadir serum cortisol predicts sustained remission in Cushing's disease. Issue 1 (10th May 2022) - Stroud, Anna; Dhaliwal, Pearl; Harvey, Richard J; Alvarado, Raquel; Jonker, Benjamin P; Winder, Mark J; Grayson, Jessica W; McCormack, Ann
Abstract : Objective: Transsphenoidal surgery (TSS) is the first-line treatment for Cushing's disease. The objectives of the study were to determine remission and recurrence rates after TSS for Cushing's disease, identify factors that predict these outcomes, and define the threshold for postoperative morning serum cortisol (MSeC) that most accurately predicts sustained remission. Methods: Records were retrospectively reviewed for consecutive adults undergoing TSS for Cushing's disease at a tertiary centre (1990–2019). Remission was defined as MSeC <138 nmol/L by 6 weeks postoperatively. Recurrence was defined as elevated 24-h urine free cortisol, lack of suppression after dexamethasone or elevated midnight salivary cortisol. Results: In this study, 42 patients (age 47 ± 13 years, 83% female) were assessed with 55 ± 56 months of follow-up. Remission occurred after 77% of primary ( n  = 30) and 42% of revision operations ( n  = 12). After primary surgery, remission was associated with lower MSeC nadir (26 ± 36 nmol/L vs 347 ± 220 nmol/L, P   < 0.01) and lower adrenocorticotropin nadir (2 ± 3 pmol/L vs 6 ± 3 pmol/L, P  = 0.01). Sustained remission 5 years after surgery was predicted by MSeC <92 nmol/L within 2 weeks postoperatively (sensitivity 100% and specificity 100%). After revision surgery, remission was predicted by lower MSeC nadir (70 ± 45 nmol/L vs 408 ± 305 nmol/L, P  = 0.03), smaller tumour diameter (3 ± 2 mm vs 15 ± 13 mm, P  = 0.05) and absence of cavernous sinus invasion (0% vs 71%, P  = 0.03). Recurrence after primary and revision surgery occurred in 17% and 20% of patients respectively. Conclusions: Lower postoperative MSeC nadir strongly predicted remission after both primary and revision surgery. Following primary surgery, an MSeC <92 nmol/L within 2 weeks predicted sustained remission at 5 years. MSeC nadir was the most important prognostic marker following TSS for Cushing's disease.